Methodological Approach to Evaluation of Clustering Potential and Efficiency Improvement Management for Development of the Regional Industry Clusters - Dyrdonova, Alena N. (International Journal of Economics and Financial Issues, 2016)
In the current environment, clustering of the economy represents a key factor in improving the competitive ability of the business entities functioning within the area whilst enhancing the interconnections between them and giving a new impulse to development of the regions. This paper offers a proven model of comprehensive evaluation of clustering potential of the regional economic systems, including a method of calculation and analysis of the parameters relating to production and resource, manpower, investment and financial potentials. Furthermore, effects of creation of an industry cluster are determined with respect to each individual participant and territory on the whole, which include economic, research and technology, innovative, social and environmental aspects. Future priority orientations of development of the region are also defined. In the authors’ opinion, formation and growth of the territorial clusters will provide a number of advantages for the regional economy, such as creation of new job places, manufacturing new types of products, development of the regional infrastructure, improvement of R&D level, effectiveness of R&D findings implementation etc. Keywords: region, cluster, clustering, clustering potential. JEL Classifications: C38, C52, O3